Short-Term Surgical Outcomes for Lobectomy Between Robot-Assisted Thoracic Surgery and Uniportal Video-Assisted Thoracoscopic Surgery - Zhang, Fan; Xu, Lin; Lu, Hongda; Ma, Anqun; Wang, Gongchao (Frontiers in Oncology, 2022)
Objectives To evaluate the short-term outcomes of uniportal video–assisted thoracoscopic surgery (UVATS) and Da Vinci robot–assisted thoracoscopic surgery (RATS) in lobectomy and lymph node (LN) dissection. Methods The two groups of patients with primary non-small cell lung cancer (NSCLC; RATS group, UVATS group) were matched by the propensity score to compare LN dissection and recent clinical outcomes. The results were analyzed by univariate analysis. From November 2020 to November 2021, 412 NSCLC patients (54 RATS and 358 UVATS) from a single institution of the Provincial Hospital affiliated with Shandong First Medical University were included in the analysis. Age, sex, lung lobe, surgical resection scope, solid nodules, and core tumor ratios were matched according to different surgical methods. Results From November 2020 to November 2021, 412 patients with NSCLC (54 RATS, 358 UVATS) from the Provincial Hospital affiliated with Shandong First Medical University were included in the analysis. According to our matching results, LN dissection was more thorough in the RATS group. Conclusion RATS has potential advantages over UVATS in radical lung cancer surgery.